The Effect of Promotion and E-Service Quality in TikTok Towards Customer Loyalty of Skintific - soewandi, verena; ratna wijayanti, ra afera; affandi, muhammad (LIAISON JOURNAL OF BEST, 2024)
This thesis aims to examine the effect of promotion and e-service quality in the popular social media platform TikTok on the customer loyalty of a skincare brand called Skintific. The study will investigate the impact of promotional activities conducted by Skintific on TikTok, as well as the quality of customer service provided through this digital platform. By analyzing customer perceptions and behaviors, the research intends to shed light on how these factors contribute to enhancing or diminishing customer loyalty. The study’s findings will be useful in providing valuable insights for skincare brands in leveraging TikTok as a promotional tool and maintaining customer loyalty in the highly competitive online marketplace. The results of this research can provide valuable information to Skintific and to all brands who would like to focus on carrying out marketing and maintain customer loyalty through the use of social media specifically TikTok. Several recommendations can be made based on these findings to improve Skintific's customer loyalty on TikTok. To begin, it is critical to develop effective promotional strategies that appeal to the TikTok target audience, taking into account their preferences and expectations. Furthermore, Skintific should focus on developing strong customer relationships on TikTok by actively engaging with their audience, responding to comments and messages, and sharing valuable and interesting content on a regular basis. Keywords: Promotion; E-Service Quality; Customer Loyalty; Integrated Marketing Communication; Liaison Journal of Best; International University Liaison Indonesia